Efficacy of Diethylcarbamazine in Allergic Rhinitis as an Adjuvant to Antihistamines : A Comparative Study - Jude Anselm Shyras D; Subramonia Biju C; Antlin Reshma; Senthil Kanitha M (Research Center for Rational Use of Drugs (RCRUD), 2022)
Background: Allergic rhinitis is a type of inflammation in the nose that occurs when the immune system overreacts to allergens in the air. Underlying mechanism involves IgE antibodies that attach to allergen resulting in release of histamine from mast cells. Signs and symptoms include a runny or stuffy nose, sneezing, redness and watering of eyes. Symptom onset is often within minutes following allergen exposure and can affect sleep and ability to work or study. People with allergic rhinitis may have associated asthma, allergic conjunctivitis, atopic dermatitis.  The study aims to know the efficacy of diethyl carbamazine in reducing the severity of symptoms in patients with allergic rhinitis when added to the antihistaminic treatment. Methods: This is a single blind randomized control trial study involving 50 allergic rhinitis patients between 13-60 years as cases and 50 as controls. The patients were classified as mild, moderate and severe based on the severity of symptoms. The cases were prescribed Tablet Diethyl carbamazine 300mg along with Tablet cetrizine 10mg for a period of 21 days. The controls were prescribed Tablet cetrizine 10mg with placebo. Patients were followed up for 3 months and watched for any reduction in the severity of symptoms. Results were compared between the study and control groups.  Results: Out of 50 patients in the study group, 20 cases showed improvement, 30 cases did not show any improvement; Out of 50 controls, 6 showed improvement and 44 didn't show any improvement. P value is significant (0.003). Conclusion: Diethyl carbamazine is an ant filarial drug which is found to have an effect in reducing the mediators of inflammation thereby useful in reducing the severity of symptoms in allergic rhinitis, as an adjuvant.